2013
DOI: 10.1186/gb-2013-14-7-r73
|View full text |Cite
|
Sign up to set email alerts
|

VlincRNAs controlled by retroviral elements are a hallmark of pluripotency and cancer

Abstract: BackgroundThe function of the non-coding portion of the human genome remains one of the most important questions of our time. Its vast complexity is exemplified by the recent identification of an unusual and notable component of the transcriptome - very long intergenic non-coding RNAs, termed vlincRNAs.ResultsHere we identify 2,147 vlincRNAs covering 10 percent of our genome. We show they are present not only in cancerous cells, but also in primary cells and normal human tissues, and are controlled by canonica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
122
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(131 citation statements)
references
References 49 publications
8
122
0
1
Order By: Relevance
“…ERVs and other TEs can promote expression of RNAs antisense to coding genes (Fig. 3C) (130) and a number of more-recent studies indicate that ERV LTRs are overrepresented as a source of transcriptional promoters for lncRNAs (186,187,188). Although many such RNAs could simply be the result of "transcriptional noise" and have no function, regulatory roles for some specific cases are being revealed.…”
Section: Erv/ltr Mediated Gene Regulationmentioning
confidence: 99%
“…ERVs and other TEs can promote expression of RNAs antisense to coding genes (Fig. 3C) (130) and a number of more-recent studies indicate that ERV LTRs are overrepresented as a source of transcriptional promoters for lncRNAs (186,187,188). Although many such RNAs could simply be the result of "transcriptional noise" and have no function, regulatory roles for some specific cases are being revealed.…”
Section: Erv/ltr Mediated Gene Regulationmentioning
confidence: 99%
“…We have recently shown that LTRs are massively transcribed in embryonic stem cells and iPS cells, some of which are involved in the maintenance of pluripotency (Fort et al 2014). Other studies demonstrated a high activity of distinct LTR subfamilies in stem cells using several different methods, including RNA-seq (Kelley and Rinn 2012;St Laurent et al 2013), DNase-seq (Jacques et al 2013), and MeDIP-seq (Xie et al 2013). Furthermore, an appropriate activation of LTRs is essential for iPS reprogramming (Lu et al 2014;Ohnuki et al 2014), suggesting that the expression of LTRs might be associated with cancerous features, such as poor differentiation and high proliferation potency.…”
mentioning
confidence: 99%
“…One interesting direction is to explore their potential involvement in nuclear architecture under various physiological or pathological conditions. For example, the lncRNA VAD, which belongs to the recently discovered very long intergenic ncRNAs (vlincRNAs) (St Laurent et al, 2013), is required to maintain oncogene-induced senescence (Lazorthes et al, 2015). VAD activates the master gene INK4 in trans, presumably by promoting the removal of repressive H2A.Z at this locus (Lazorthes et al, 2015).…”
Section: Discussionmentioning
confidence: 99%